MOTIVASI DAN PERSEPSI TERHADAP MINAT MAHASISWA MENGIKUTI BREVET PAJAK - Winatha, Felicia Elisabeth; Sujana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.10.TAHUN.2024, 2024)
The amount of tax consultants in Indonesia is quite low because the number of participants who pass the USKP is still low. Tax brevet is one way that can be done to increase understanding of taxation. The purpose of this study was to determine the effect of economic motivation, career motivation, student perceptions, and cost perceptions on students’ interest in joining tax brevet. The sample for this research was 161 students of the Bachelor of Accounting Study Program, Faculty of Economics and Business, Udayana University, class of 2019, which were determined through a purposive sampling technique. This study collected data by distributing questionnaires, which were analyzed using multiple linear regression methods. The results of the study revealed that economic motivation, career motivation, and student perceptions had a positive effect and cost perception had a negative effect on students’ interest in joining tax brevet. The theoretical implication of this research lies in its support for the theory of planned behavior, Maslow's motivation theory, and attribution theory for its ability to explain the variables in this study. The practical implication of this research lies in its function which can be used as additional information for academics, students, and the general public.